Exploration of Alternative Financing Strategy for the Small and Medium Enterprises in South Africa - Xolo, Siyavuya (Research of GSB, 2018)
Small and Medium Enterprises (SMEs) are the most talk about businesses which are vital for economic growth at the same time are faced with challenges to obtain finance from the financial institutions. The research intends making a contribution to assist coming up with a possible way and strategy to obtain funds and devise an implementation plan to make funds accessible to the SMEs. Different studies point to almost similar causes that lead to the challenges experienced by the SMEs. Everyone that has shown an interest in the subject of the SMEs has in a way, formally or informally, proposed some kind of intervention mechanism. Different things are being tried at the same time in order to speed up the process although the progress is not to the level of satisfactory otherwise there would be no need to undertake the research. The focus of the research is on the SMEs in South Africa. In preparation for this research, a literature review on various aspects of the SMEs was covered to ensure that whatever plan of action is going to be proposed there is no repetition of work that has already been done; instead it can be aligned to some ideas that have already been suggested. The research explores possible ways to source funds that will be used towards financing the SMEs in South Africa. A suggested implementation strategy is to ensure that the impact is significant in improving the situation. Details of who will be responsible for what and the possible sources of funds are provided in Chapters four and five. The research is more on devising the solution for the SMEs based on the readily available literature review information and the opinions of the researcher, for that reason there is no need for surveys or preparation of questionnaires for submission to some of the financial institutions. A great deal of work has been done in this area of the SMEs and it is clear as to what is the real challenge. Primary and secondary data are relevant for this research. The research is undertaken with the understanding that people will have different ideas and preferences for different reasons; hence it is expected to have divided views on what is in this research report. In addressing global issues or issues of national interest a collaborative effort is crucial, and where possible innovative ideas are to be shared. The whole world is calling for innovative ideas; the more ideas are put on the table the better, then a judgement call will be made to implement or not implement. There are those who believe that government should intervene by reviewing policies to correct the market failure and some see the establishment of a financial institution solely intended for the SMEs. What does not come out clearly is how the institution will be funded considering that there are so many challenges in South Africa that need government intervention and the resources are limited. Based on this, the researcher identified options to be used to generate funds to be used to finance the SMEs, details are in Chapter four, and then the amount to be obtained from each option was estimated, details are in Chapter five. The strategy to manage financing of the SMEs is provided in Chapter Six and the discussion of the results which are found in different sections of this report is in Chapter Seven, followed by the conclusion.